HEALTH EDUCATION ABOUT FREE SEX FOR ADOLESCENTS AT SMK SETYA BHAKTI 2 AND SMK 16 EAST JAKARTA - Suryani Hartati; Ajeng Dwi Retnani (Darmabakti Cendekia)
Background: Adolescence is an important transitional period due to excessive curiosity. Adolescents' curiosity about sexual life is increasing along with the information on social media. The problem of premarital sexual behavior in adolescents is very important to prevent because it can lead to early pregnancy and sexually transmitted diseases. Objective: This activity aims to increase knowledge about the impact of premarital sexual behavior and its prevention on students of SMK Setya Bhakti 2 and SMK 16 East Jakarta. Method: Community service activities began with data collection at schools in the East Jakarta area, then providing direct education to grade XII students. All participants were given a pre-test and post-test as an evaluation. Results: The activity was held on February 16 2024, attended by 38 students of SMK Setya Bhakti 2 and 40 students of SMK 16 East Jakarta. The average age of participants was 17-18 years. More than fifty percent participants had poor knowledge regarding free sex (61.5%), then increased to be good knowledge by 77.0%. Conclusion: Premarital sexual education for grade XII students can increase their knowledge so that adolescents can avoid the dangers of free sexual behavior.